Contemporary Risk Factors of High Blood Pressure for Youth Group (18-24) Years for Students of Technical Institute in Baquba and University of Diyala - yasin, oras (Iraqi National Journal of Nursing Specialties, 2017)
Objective: This study aimed to investigate the relationship between high blood pressure anddifferent variables, such as (weight, smoking, amount of salt and water taken daily, and numberof hours of natural sleep per person) for young people.Methodology: The study was conducted on students at the student community of the TechnicalInstitute in Baquba and the University of Diyala during the period from September 2015until June 2016. The patients ranged in age from 18-24 years. All data were collected througha questionnaire that included the main reasons and periodic follow-up of the disease.Results: The total number of samples was 450.The results showed that 33% of all sampleshave high blood pressure. The relationship between the causes and the high blood pressurewas as follows: High weight showed 53%, smoking 40%, daily water intake 61%, daily saltintake 29%. Also, the effect of reducing sleep rate was 83% and it presented the highest percentagecompared with other causes.Recommendations: The study recommends to do further study promote the healthy lifestyleof the youth and confirm on the healthy habits by raising awareness among university studentsto reduce these causes of early infection with high blood pressure.